Performance of The Agency’s Regional Revenue Management Fieldregional Finance of South Kalimantan Province - Ade Hermawan; Jamili, Muhammad; Bakhtiar (Formosa Journal of Multidisciplinary Research, 2024)
The management of original regional income in South Kalimantan Province is the responsibility of regional government officials, especially the Regional Finance Agency of South Kalimantan Province. All local original revenue management processes are of course influenced greatly by the performance of the South Kalimantan Provincial Regional Financial Agency so that a decrease or increase in a region's original regional income is more or less influenced by the performance of the South Kalimantan Provincial Regional Financial Agency . This research aims to study and examine the Performance of the Regional Revenue Management Sector of the Regional Financial Agency of South Kalimantan Province. The method used in this research is the descriptive method. The data obtained in this research are primary data and secondary data. The data collection techniques used are documentation and interviews. The analysis technique used is qualitative analysis. The Regional Revenue Management Sector of the Regional Financial Agency of South Kalimantan Province has good accountability, is able to fulfill financial obligations well, has good honesty, applies the principles of efficiency and effectiveness well, and control activities are carried out well too. So overall it can be concluded that the performance of the Regional Revenue Management Sector of the Regional Financial Agency of South Kalimantan Province all leads to good performance.